The legal objectives derived from the narrations of Al-Rabi’ bint Mu’awwidh and Umm Qays - Samira Jassim Mohammed; Othman Khudair Muzal (Islamic Sciences Journal, 2025)
The objectives of Islamic law (maqasid al-shari'ah) have significant implications for understanding the text, strengthening faith, warning against sins and transgressions, and urging the maintenance of kinship ties. Islam came to preserve the five essentials (life, religion, and religion), thus guaranteeing the individual a free and dignified life based on justice and equality, leading to the establishment of a society characterized by virtuous morals. This research aims to study the objectives of Islamic law derived from the narrations of the two female companions, Al-Rubayyi' bint Mu'awwadh and Umm Qays bint Mihsan (may God be pleased with them). It seeks to demonstrate the contribution of female companions in transmitting the Sunnah and understanding its objectives, as well as the role of women in building and consolidating Islamic jurisprudence. The research revealed a number of objectives of Islamic law and concluded that the narrations of Al-Rubayyi' bint Mu'awwadh and Umm Qays bint Mihsan represent an important source for understanding the objectives of Islamic law and highlight the comprehensiveness of Islamic legislation.